HIGH ALKALINE PHOSPHATASE POST KASAI PROCEDURE, SHOULD WE LOOK BEYOND THE LIVER? - AW, Muhammad Ammar; A, Lordudas Alexi; EX, Pang Calvin (Journal of the ASEAN Federation of Endocrine Societies, 2019)
INTRODUCTION Metabolic bone disease (MBD) is a recognized complication in patients post Kasai procedure. In biliary atresia (BA), metabolic disturbance is caused by impairment of the passage of bile salts into the alimentary canal causing inadequate emulsification of fat and thus incomplete absorption of vitamin Progressively, liver cirrhosis develops in BA leading to further impairment of hydroxylation of vitamin D. METHODOLOGY We report a 5-year, 7-month-old girl with post Kasai procedure done successfully at Day 71 of life for Biliary Atresia with incidental increase in ALP during routine clinic review. Unfortunately no serial liver function was done as she had defaulted follow up. She did not sustain any fractures before. Clinically she was pink and not jaundiced. She was not clubbed but small for age. Per abdominal examination yield no significant findings apart from healed rooftop scar. Her wrists were swollen. No rachitic rosary noted. RESULTS Full blood count revealed Hemoglobin (Hb) 13.4 g/dL and platelets of 329 103 /UL. Liver function test revealed Alanine Aminotransferase (ALT) 26.31 U/L, Aspartate aminotransferase (AST) 61.77 U/L, alkaline phosphate (ALP) 6996 U/Total serum bilirubin was 5.95 umol/Direct bilirubin of 3.5 umol/L Gamma-Glutamyl-transferase (GGT) was 134 U/Coagulation profile revealed INR 0.96 and APTT 50.8 sec. Vitamin D level unfortunately was rejected and intact Parathyroid hormone was 63.6 pg/mL. Hepatobiliary Ultrasonography showed no biliary tree obstruction with cirrhotic liver. No nodular lesion. We started her on oral calcitriol 1 mcg once daily. The ALP begins to decrease from 6996 U/L to 800 U/L within two months. She has been well during outpatient review. CONCLUSION Vitamin D is essential for the bone growth and development. Sustained vitamin D deficiency in children may cause bone deformity, pain, or pathological fractures (i.e., rickets). The management of Vitamin D deficiency include oral vitamin D supplement and pamidronate (bisphosphonates). Clinicians need to remain vigilant in monitoring for MBD especially in patients post liver surgery.